The upper noble lineage in Morocco - Al-Obaidi, Asia Thamer Hadi; AL-Taai, Suaad Hadi Hassan (Al-Adab Journal, 2022)
The knowledge of lineage is a matter of great destiny, as it is a matter of acquaintance between people, and God has made learning it a virtue that no one can be ignorant of. Knowing people about their lineage is an obligatory purpose for him in his creation of us as peoples and tribes. The Prophet Muhammed urged the necessity of knowing the lineage and knowing the lineage of the Prophet’s family is of great importance to the necessity of honoring and glorifying them, for they are the best of God that He chose and preferred them over people. The branches of this dynasty spread in the east and west of the earth on the authority of our master Ali bin Abi Talib (D. 661).Our Lady Fatima al-Zahra bint Muhammed (D. 632), their two sons, Imam al-Hassan and al-Husayn, had descendants in all countries, and what concerns us here is their succession in the countries of the Maghreb, as many of their descendants emerged from the saints, the righteous, the servants, the ascetics, the working scholars, the writers, the leaders, and the rulers They even established states there, and they had a great affair.